Implementasi Manajemen Risiko Dalam Dunia Perbankan Syariah - Siti Hajar; Wirman Wirman (Peneliti.net, 2023)
Every business activity is inseparable from risks that can interfere with business continuity, including in sharia banking business activities. The characteristics of products and services in Islamic banking require identification, measurement, monitoring and risk management functions in accordance with these activities. Islamic banks always face various types of risks with various complexities inherent in their business activities. Therefore, the application of risk management in Islamic banking is one of the most important things to be applied to identify, measure, and control the various risks that will be faced. Through this paper, we discuss the theoretical risk management of Islamic banking in Indonesia and its implementation. In this journal, we also discuss the classification of risk in Islamic banks as well as the implementation of risk management agreements in Islamic banks.